A Novel Anastomosis Technique for Laparoscopic Pancreaticoduodenectomy: Case Series of Our Center's Experience - Sun, Pi-Jiang; Yu, Yan-Hua; Li, Jian-Wei; Cui, Xi-Jun (Frontiers in Surgery, 2021)
Background: Laparoscopic pancreaticoduodenectomy has developed rapidly in recent years. Postoperative pancreatic fistula is still the most dangerous complication of laparoscopic pancreaticoduodenectomy. Baumgart pancreaticojejunostomy is considered one of the safest anastomosis procedures, with low rates of pancreatic fistula. We modified Blumgart pancreaticojejunostomy and applied the modified procedure during laparoscopic pancreaticoduodenectomy. The modified procedure entailed a longitudinal U-shaped suture through the pancreas for anastomosis of the pancreatic duct and the jejunal mucosa. Methods: We prospectively collected and retrospectively analyzed the data of 120 patients who underwent laparoscopic pancreaticoduodenectomy from January 2016. The total operative time, time for complete pancreaticojejunostomy, postoperative pancreatic fistula rate, postoperative delayed gastric emptying, postoperative bleeding, postoperative length of hospital stays, and mortality within 90 days after surgery were analyzed. An analysis of laparoscopic pancreaticojejunostomy compared with open pancreaticojejunostomy is also reported. Results: In the laparoscopic pancreaticojejunostomy group, the average total operative time, the average time for complete pancreaticojejunostomy, and the average intraoperative blood loss were 271 minutes, 35.3 minutes, and 184 ml, respectively. The total postoperative clinically relevant pancreatic fistula rate was 9.2% (Grade B and C fistulas). The incidence rates of postoperative delayed gastric emptying and postoperative biliary fistula were approximately 2.5% and 1.7%, respectively. The postoperative bleeding rate was 0.83%, and the average postoperative indwelling time of the abdominal drainage tube was 7.3 days. The postoperative length of hospital stay was 10.8 days, and the mortality rate within 90 days after surgery was 0.83%. The rates of clinically relevant postoperative clinically relevant pancreatic fistula are comparable between laparoscopic and open surgery, there were no other severe postoperative complications in either group. The mean postoperative length of hospital stay was significantly shorter in the laparoscopic pancreaticojejunostomy group. Conclusion: The modified laparoscopic-adapted Blumgart anastomosis simplifies and facilitates the creation of the pancreaticojejunostomy in laparoscopic pancreaticoduodenectomy. The rates of clinically relevant postoperative pancreatic fistula are comparable with those obtained by open surgery, and length of stay are shoter.